Family ownership and firm performance: Empirical evidence from Western European corporations - Maury, Benjamin (Journal of Corporate Finance, 2006)
This paper empirically examines how family-controlled firms perform in relation to firms with nonfamily controlling shareholders in Western Europe. The sample consists of 1672 non-financial firms. Active family control is associated with higher profitability compared to nonfamily firms, whereas passive family control does not affect profitability. Active family control continues to outperform nonfamily control in terms of profitability in different legal regimes. Active and passive family control is associated with higher firm valuations, but the premium is mainly due to economies with high shareholder protection. The benefits from family control occur in nonmajority held firms. These results suggest that family control lowers the agency problem between owners and managers, but gives rise to conflicts between the family and minority shareholders when shareholder protection is low and control is high.